Cardiac Subtype-Specific Modeling of Kv1.5 Ion Channel Deficiency Using Human Pluripotent Stem Cells - Marczenke, Maike; Piccini, Ilaria; Mengarelli, Isabella; Fell, Jakob; Röpke, Albrecht; Seebohm, Guiscard; Verkerk, Arie O.; Greber, Boris (Frontiers in Physiology, 2017)
The ultrarapid delayed rectifier K+ current (IKur), mediated by Kv1.5 channels, constitutes a key component of the atrial action potential. Functional mutations in the underlying KCNA5 gene have been shown to cause hereditary forms of atrial fibrillation (AF). Here, we combine targeted genetic engineering with cardiac subtype-specific differentiation of human induced pluripotent stem cells (hiPSCs) to explore the role of Kv1.5 in atrial hiPSC-cardiomyocytes. CRISPR/Cas9-mediated mutagenesis of integration-free hiPSCs was employed to generate a functional KCNA5 knockout. This model as well as isogenic wild-type control hiPSCs could selectively be differentiated into ventricular or atrial cardiomyocytes at high efficiency, based on the specific manipulation of retinoic acid signaling. Investigation of electrophysiological properties in Kv1.5-deficient cardiomyocytes compared to isogenic controls revealed a strictly atrial-specific disease phentoype, characterized by cardiac subtype-specific field and action potential prolongation and loss of 4-aminopyridine sensitivity. Atrial Kv1.5-deficient cardiomyocytes did not show signs of arrhythmia under adrenergic stress conditions or upon inhibiting additional types of K+ current. Exposure of bulk cultures to carbachol lowered beating frequencies and promoted chaotic spontaneous beating in a stochastic manner. Low-frequency, electrical stimulation in single cells caused atrial and mutant-specific early afterdepolarizations, linking the loss of KCNA5 function to a putative trigger mechanism in familial AF. These results clarify for the first time the role of Kv1.5 in atrial hiPSC-cardiomyocytes and demonstrate the feasibility of cardiac subtype-specific disease modeling using engineered hiPSCs.